The Role of Social Workers in Giving Service to Elders - Siti Aminatun; Chulaifah Chulaifah (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2015)
This research is meant to describe the role of social workers in giving service to elders. The negligence that suffered by elder needs attention because of his or her backwardness and empowerness to fulfill their living needs. A place to live is a basic need of elders that should be fulfilled to assure their living welfare so that elder can enjoy his or her old daysin safety and peace living condition. Neglected elder who does not have a house to live and no one willing to give him or hersocial service, his or her condition will become worse. Social workers are needed to minimize his or her negligence. Research location determined purposively at Panti Wreda Budi Dharma (Social Institution), based on the consideration that this institution has commited social workers in giving service to elders. Data are gathered through interview, observation, and documentary analyses. The informants consisted elders, institutional managements, social workers, who give services to elders. Data are analyzed through qualitative techniques on the role of social workers giving service to elders. The research shows that social workers at this institution have a significant role in giving services to the elders, with several roles they have done the elders can feel part of the family at the institution, live in peace, welfare, safety, and fulfilled all their living needs and have a place to stay long live. Elders and their families get satisfaction psychologically with services given by social workers and institutional managements. It is recommended that the Ministry of Social Affaris should give attention and support to social workers working at that institution, though they are not social work educated but practically they work as social workers. The support can be manifested to give social workers a chance to participate in social work formaleducation and training to improve their capacity that will have an impact on their profession relating to humanity.